Risk factors for lower limb musculoskeletal injuries in novice runners: a prospective study - Greybe, Rykie (Division of Physiotherapy, 2015)
The aim of this study was to identify the possible risk factors for the development of lower limb musculoskeletal injuries in novice runners. The specific objectives of this study were: (a) to describe the demographic and training characteristics of novice runners; (b) to establish the incidence of self-reported running-related injuries in novice runners; (c) to determine if specific intrinsic factors, namely age, gender, body mass index, quadriceps angle, foot alignment, hamstring flexibility, balance, muscle power and a history of previous injury were risk factors for lower limb musculoskeletal injuries in novice runners; and (d) to determine if specific extrinsic factors, namely training frequency, session duration, and intensity were risk factors for developing lower limb musculoskeletal injuries in novice runners.